Pengawasan pada Pengelolaan Penerangan Jalan Umum Oleh Dinas Perumahan Rakyat, Kawasan Permukiman Kebersihan dan Pertamanan Kota Tanjungpinang - Nurul Aulia Putri; Jamhur Poti; Fitri Kurnianingsih (Majelis: Jurnal Hukum Indonesia, 2025)
This research aims to explain the management control of public street lighting (PJU) in Tanjungpinang City. PJU is an important element in creating safety and comfort for the community in economic, social and traffic activities. However, not all areas in Tanjungpinang have been covered by PJU facilities, and many PJUs are damaged. This research uses the control theory by T. Hani Handoko (2010) which consists of 1) Feedforward control, 2) Concurrent control, and 3) Feedback control. The research method used is qualitative with data collection techniques of observation, interview, and documentation. The results showed that PJU management control in Tanjungpinang City was not optimal. In feedforward control, there are obstacles such as the lack of community participation in PJU development planning. In concurrent control, coordination between the community, the Housing, Settlement Areas, Cleanliness and Parks Office, consultants, PLN, and contractors has not been optimal. While in feedback control, the lack of community participation in reporting damage and maintenance of PJU is only done based on reports or surveys with priority on protocol roads. Routine supervision is limited due to limited human resources, and response to public complaints is slow. This study concludes that the improvement of PJU management requires good planning and active community participation.